2022
DOI: 10.1002/ange.202209629
|View full text |Cite
|
Sign up to set email alerts
|

Selective CO2Electroreduction to Ethanol over a Carbon‐Coated CuOxCatalyst

Abstract: The design of efficient copper(Cu)-based catalysts is critical for CO 2 electroreduction into multiple carbon products. However, most Cu-based catalysts are favorable for ethylene production while selective production of ethanol with high Faradaic efficiency and current density still remains a great challenge. Herein, we design a carbon-coated CuO x (CuO x @C) catalyst through one-pot pyrolysis of Cu-based metal-organic framework (MOF), which exhibits high selectivity for CO 2 electroreduction to ethanol with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…This indicates that the oxidation state Cu on the catalyst surface is partially reduced, forming the Cu–Cu 2 O interface; therefore, the metal-oxide interface effect can effectively improve the formation rate of C 2+ from the CO 2 RR. 20 At the same time, the elements overlap each other in the EDX mapping of Cu 2 O@SiO 2 –NH 2 and Cu 2 O@SiO 2 samples, which proves that the Cu 2 O@SiO 2 –NH 2 catalyst still maintains a complete coating structure after the CO 2 RR (Fig. S14e, f and S15e†).…”
Section: Resultsmentioning
confidence: 79%
See 1 more Smart Citation
“…This indicates that the oxidation state Cu on the catalyst surface is partially reduced, forming the Cu–Cu 2 O interface; therefore, the metal-oxide interface effect can effectively improve the formation rate of C 2+ from the CO 2 RR. 20 At the same time, the elements overlap each other in the EDX mapping of Cu 2 O@SiO 2 –NH 2 and Cu 2 O@SiO 2 samples, which proves that the Cu 2 O@SiO 2 –NH 2 catalyst still maintains a complete coating structure after the CO 2 RR (Fig. S14e, f and S15e†).…”
Section: Resultsmentioning
confidence: 79%
“…Upon applying the Cu 2 O-BN catalyst for the CO 2 RR process, the ratio of C 2 H 4 /CO increased by 1.62 times compared with that of the Cu 2 O catalyst. Similarly, Zang et al 20 designed a carbon-coated CuO x (CuO x @C) catalyst and the carbon layer on the catalyst surface effectively stabilized Cu + species, thereby facilitating the C–C coupling process. In the CO 2 RR process, the FE of ethanol reached 46%, and the partial current density reached 166 mA cm −2 .…”
Section: Introductionmentioning
confidence: 99%
“…The main byproducts of this HDO process are alkanes formed after the continuous deoxygenation of alcohols. , The adsorption capacity of catalysts for lipids is positively correlated with the selectivity of alkanes, , so we reason that the moderate adsorption capacity of catalysts for lipids is one of the key factors in controlling fatty alcohol selectivity. Coating a carbon layer on the surface of the catalyst is one of the main strategies to change the substrate adsorption capacity. Meanwhile, the carbon coating can stabilize metal active species, thereby significantly reducing deactivation. …”
Section: Introductionmentioning
confidence: 99%
“…The carbon-supported nano Cu or CuO x catalysts rely on the absorption features of the *CO and *H on the Cu atoms, these catalysts could enhance their selectivity of C 2+ products and EtOH 16,17 . Furthermore, related researches have revealed that their low coordination Cu atoms in Cu nanoparticles are the source of CO 2 RR catalytic active sites 18,19 . The decreasing size of metal nanoparticles increases the speci c surface of the metal with more active atoms, enhancing the catalytic activity [20][21][22] .…”
Section: Introductionmentioning
confidence: 99%